2000
DOI: 10.1074/jbc.275.18.13564
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-binding Growth-associated Molecule Contains Two Heparin-binding β-Sheet Domains That Are Homologous to the Thrombospondin Type I Repeat

Abstract: Heparin-binding growth-associated molecule (HB-GAM) is an extracellular matrix-associated protein implicated in the development and plasticity of neuronal connections of brain. Binding to cell surface heparan sulfate is indispensable for the biological activity of HB-GAM. In the present paper we have studied the structure of recombinant HB-GAM using heteronuclear NMR. These studies show that HB-GAM contains two ␤-sheet domains connected by a flexible linker. Both of these domains contain three antiparallel ␤-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
96
0
21

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 113 publications
(125 citation statements)
references
References 50 publications
8
96
0
21
Order By: Relevance
“…However, both are all-␤ proteins with a central ␤-sheet and three disulfide bridges. TSR modules are likely to have a ␤-sheet structure, as well, based on their homology with the all-␤ proteins HB-GAM (heparin-binding growth-associated molecule) and midkine (43). If this proposition is correct, the O-fucosylation site in TSRs is located in a loop between the first two ␤-sheets.…”
Section: Discussionmentioning
confidence: 99%
“…However, both are all-␤ proteins with a central ␤-sheet and three disulfide bridges. TSR modules are likely to have a ␤-sheet structure, as well, based on their homology with the all-␤ proteins HB-GAM (heparin-binding growth-associated molecule) and midkine (43). If this proposition is correct, the O-fucosylation site in TSRs is located in a loop between the first two ␤-sheets.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of heparin binding growth-associated molecule with heparin is mediated primarily by ␤-sheet domains homologous to the thrombospondin type I repeat. Because it contains similar domains, those conclusions were also extended to midkine (41). For the midkine carboxyl-terminal domain, it has been suggested that the conserved tryptophan in the first ␤-strand and downstream basic amino acids in the second ␤-strand are involved in the formation of a heparin-binding surface (40).…”
Section: Wisp-1 Binds To Decorin At the Surface Of Human Skinmentioning
confidence: 99%
“…This motif is thought to be involved in binding to sulfated glycoconjugates (8) and could constitute a dermatan sulfate or a second heparin binding domain for the CCN family. Recently, the three-dimensional structure of the heparin-binding growthassociate molecule and midkine were resolved (40,41). The interaction of heparin binding growth-associated molecule with heparin is mediated primarily by ␤-sheet domains homologous to the thrombospondin type I repeat.…”
Section: Wisp-1 Binds To Decorin At the Surface Of Human Skinmentioning
confidence: 99%
See 1 more Smart Citation
“…NMR experiments have clearly demonstrated that the HARP molecule is organized into two ␤-sheet domains linked by a flexible linker, and this structure is maintained through five intrachain disulfide bonds (19). Each ␤-sheet domain contains a heparin-binding site, which plays a role in the modulation of HARP mitogenic activity (20).…”
mentioning
confidence: 99%